2017
DOI: 10.1038/s41598-017-11793-x
|View full text |Cite
|
Sign up to set email alerts
|

An autocrine purinergic signaling controls astrocyte-induced neuronal excitation

Abstract: Astrocyte-derived gliotransmitters glutamate and ATP modulate neuronal activity. It remains unclear, however, how astrocytes control the release and coordinate the actions of these gliotransmitters. Using transgenic expression of the light-sensitive channelrhodopsin 2 (ChR2) in astrocytes, we observed that photostimulation reliably increases action potential firing of hippocampal pyramidal neurons. This excitation relies primarily on a calcium-dependent glutamate release by astrocytes that activates neuronal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 81 publications
2
53
0
Order By: Relevance
“…In addition to an increase in SIC frequency in nearby neurons, selective astrocyte activation via either G q DREADD or G i/o DREADD signaling led to an increase in action potential firing of hippocampal neurons. While most reports of neuronal‐glial interactions have shown synaptic transmission regulation by astrocytes (Araque et al, ), present results add to recent studies showing that astrocytes can also regulate neuronal firing and network activity (Lee et al, ; Poskanzer & Yuste, , ; Shen, Nikolic, Meunier, Pfrieger, & Audinat, ; Tan et al, ). Indeed, the observed increase in astrocyte Ca 2+ activity upon CNO injection in vivo co‐occurred with an upregulated delta range of the slow‐wave activity.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition to an increase in SIC frequency in nearby neurons, selective astrocyte activation via either G q DREADD or G i/o DREADD signaling led to an increase in action potential firing of hippocampal neurons. While most reports of neuronal‐glial interactions have shown synaptic transmission regulation by astrocytes (Araque et al, ), present results add to recent studies showing that astrocytes can also regulate neuronal firing and network activity (Lee et al, ; Poskanzer & Yuste, , ; Shen, Nikolic, Meunier, Pfrieger, & Audinat, ; Tan et al, ). Indeed, the observed increase in astrocyte Ca 2+ activity upon CNO injection in vivo co‐occurred with an upregulated delta range of the slow‐wave activity.…”
Section: Discussionsupporting
confidence: 76%
“…While most reports of neuronal-glial interactions have shown synaptic transmission regulation by astrocytes , present results add to recent studies showing that astrocytes can also regulate neuronal firing and network activity (Lee et al, 2014;Poskanzer & Yuste, 2011Shen, Nikolic, Meunier, Pfrieger, & Audinat, 2017;Tan et al, 2017). Indeed, the observed increase in astrocyte Ca 2+ activity upon CNO injection in vivo co-occurred with an upregulated delta range of the slow-wave activity.…”
Section: Discussionsupporting
confidence: 75%
“…Light‐induced astrocyte activation triggered somatic Ca 2+ elevations in EYFP ‐expressing astrocytes with mean amplitude of 225.6 ± 21.54 Δ F / F that peaked 5.6 ± 0.3 s after the onset of the stimulation (24 cells, 5 animals). Similar to CA1 (Shen et al, ), light‐triggered Ca 2+ signals in astrocyte cell body in dentate gyrus were dependent on P2Y1 receptor activation, as 2′‐deoxy‐N6‐methyladenosine 3′,5′‐bisphosphate tetrasodium salt (MRS 2179, 10 μM) reduced these responses (Figure a). Light‐evoked Ca 2+ signals could not be suppressed completely by MRS 2179.…”
Section: Resultsmentioning
confidence: 59%
“…To assess further the mechanism of TNFα action on astrocytes, we next bypassed the cytokine and tried to directly trigger glutamate release from molecular layer astrocytes by optogenetic activation of the light‐sensitive channel channelrhodopsin‐2 (ChR2). Indeed, we have recently shown that astrocyte photoactivation by ChR2 in CA1 results in a Ca 2+ ‐dependent glutamate release (Shen, Nikolic, Meunier, Pfrieger, & Audinat, ). Furthermore, this ChR2‐induced glutamate release from CA1 astrocytes, which leads to the activation of neuronal glutamate receptors, requires an autocrine P2Y1 receptor activation (Shen et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation